Strengths-Based Analysis of Student Success in Online Courses - Carol S Gering; Dani' K Sheppard; Barbara L Adams; Susan L Renes; Allan A Morotti (Online Learning, 2018)
Online courses today give a broad, diverse population access to higher education. Despite postsecondary institutions embracing this opportunity, scholarly literature reveals persistent concern over low retention rates in online courses. In response to this concern, an explanatory sequential, mixed methods study was conducted in three phases at a public research university to simultaneously explore personal, circumstantial, and course variables associated with student success from a strengths-based perspective. Existing data on student enrollments across four years were analyzed. A subset of Phase One students from a single semester were invited in the second phase to complete an assessment of non-cognitive attributes and personal perceptions, followed in the third phase by interviews among a stratified sample of successful students from the previous phase to elaborate on factors impacting their success. Quantitative analyses identified seven individual variables with statistical and practical significance for online student success. Interestingly, the combination of factors classified as predictive of success changed with student academic standing. The impact of differential success factors across academic experience may explain mixed results in previous studies. The themes that emerged from the interviews with students were congruent with quantitative findings. A unique perspective was shared when students discussed “teaching themselves,” providing additional insight into perceptions of teaching presence not formerly understood. The combination of a more contextual research approach, a strengths-based perspective, and insights from student perceptions yielded implications for educational practice.